2020
DOI: 10.1097/iae.0000000000002487
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clinically Unsuspected Retinal Neovascularization With Wide-Field Optical Coherence Tomography Angiography

Abstract: Purpose: To evaluate wide-field optical coherence tomography angiography (OCTA) for detection of clinically unsuspected neovascularization (NV) in diabetic retinopathy (DR). Methods: This prospective observational single-center study included adult patients with a clinical diagnosis of nonproliferative DR. Participants underwent a clinical examination, standard 7-field color photography, and OCTA with commercial and prototype swept-source devices. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 29 publications
0
24
0
8
Order By: Relevance
“…According to the authors, clinical examination may have missed these vessels due to previous treatment with anti-VEGF, which may have altered their visibility. (13) In our cohort, none of the patients diagnosed clinically with NPDR were previously treated with anti-VEGF. It is still unclear whether the sensitivity of OCTA in detecting small neovascularisation not visible on clinical examination has clinical significance and if this neovascularization should be treated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the authors, clinical examination may have missed these vessels due to previous treatment with anti-VEGF, which may have altered their visibility. (13) In our cohort, none of the patients diagnosed clinically with NPDR were previously treated with anti-VEGF. It is still unclear whether the sensitivity of OCTA in detecting small neovascularisation not visible on clinical examination has clinical significance and if this neovascularization should be treated.…”
Section: Discussionmentioning
confidence: 96%
“…(4), (12) OCTA may potentially facilitate staging of DR or even detection of early DR changes prior to clinically detectable retinopathy. (13) Thus, it shows promise in supplementing clinical examination by potentially replacing FFA for the diagnosis and monitoring of DR. Until recently, this was not achievable due to the limited field of view of earlier devices. However, a swept-source OCTA (SS-OCTA) device has become available, allowing for montaging of several scans in real-time, thus providing almost 80 degrees field of view in a single scan.…”
Section: Introductionmentioning
confidence: 99%
“…We found that patients with higher severity of DR had a higher MAS and segmentation errors were more frequent in eyes with PDR. Because wide-field SS-OCTA has been used in the diagnosis and follow-up of DR, 2,7,8,12,16 it is necessary to understand the factors that contribute to both segmentation and motion artifacts of montage images in order to ensure meaningful and reliable results. This is particularly important to accurately incorporate wide-field OCTA into our clinical decision making in DR patients as we examine small, quantitative differences in NV and nonperfusion areas.…”
Section: Discussionmentioning
confidence: 99%
“…( Figure 5) Tan and co-workers further improved the diagnostic performance of widefield OCTA in detecting nonperfusion areas, by removing the influence of larger retinal vessels from capillaries in OCTA scans [92]. Furthermore, widefield OCTA resulted in the higher detection of retinal neovascularization than on clinical examination, which suggests that widefield OCTA could be considered for the purpose of early detection of neovascularization [94,95]. Of note, the widefield fluorescein angiography remains a vital clinical tool in its ability to detect both peripheral retinal nonperfusion and eventual peripheral active neovascularization, which remains difficult to visualize clinically and is less accurately identified with widefield OCTA.…”
Section: Peripheral Retinal Nonperfusionmentioning
confidence: 99%